Systems Engineering Roles in Software Organizations Delivering Service Products. Issue 2 (6th August 2021) - Bouyaud, Mickael; White, Brian E.
ABSTRACT: The software industry has been experiencing several transformations. Development teams now often autonomously deliver business capabilities to software service systems. The Unicorn Project, a best‐seller, tells how a retail company transformed into an Agile and DevOps organization. This paper uses a model from the systems engineering toolset to understand those organizational changes and proposes an evolution of the systems engineering discipline to increase the value provided by this type of organization.